Thrombospondin-1 Signaling Through the Calreticulin/LDL Receptor Related Protein 1 Axis: Functions and Possible Roles in Glaucoma - Murphy-Ullrich, Joanne E. (Frontiers in Cell and Developmental Biology, 2022)
Thrombospondin-1 (TSP-1) is a matricellular extracellular matrix protein. Matricellular proteins are components of the extracellular matrix (ECM) that regulate key cellular functions and impact ECM organization, but which lack direct primary structural roles in the ECM. TSP-1 expression is upregulated in response to injury, hypoxia, growth factor stimulation, inflammation, glucose, and by reactive oxygen species. Relevant to glaucoma, TSP-1 is also a mechanosensitive molecule upregulated by mechanical stretch. TSP-1 expression is increased in ocular remodeling in glaucoma in both the trabecular meshwork and in the optic nerve head. The exact roles of TSP-1 in glaucoma remain to be defined, however. It plays important roles in cell behavior and in ECM remodeling during wound healing, fibrosis, angiogenesis, and in tumorigenesis and metastasis. At the cellular level, TSP-1 can modulate cell adhesion and migration, protease activity, growth factor activity, anoikis resistance, apoptosis, and collagen secretion and matrix assembly and cross-linking. These multiple functions and macromolecular and receptor interactions have been ascribed to specific domains of the TSP-1 molecule. In this review, we will focus on the cell regulatory activities of the TSP-1 N-terminal domain (NTD) sequence that binds to cell surface calreticulin (Calr) and which regulates cell functions via signaling through Calr complexed with LDL receptor related protein 1 (LRP1). We will describe TSP-1 actions mediated through the Calr/LRP1 complex in regulating focal adhesion disassembly and cytoskeletal reorganization, cell motility, anoikis resistance, and induction of collagen secretion and matrix deposition. Finally, we will consider the relevance of these TSP-1 functions to the pathologic remodeling of the ECM in glaucoma.